1995
DOI: 10.1073/pnas.92.2.626
|View full text |Cite
|
Sign up to set email alerts
|

Disregulation of leukosialin (CD43, Ly48, sialophorin) expression in the B-cell lineage of transgenic mice increases splenic B-cell number and survival.

Abstract: Leukosialin (also known as Ly48, CD43, and sialophorin) is a major cell surface sialoglycoprotein found on a variety of hematopoietically derived cells. The precise function of this molecule is poorly understood but it has been implicated in cell proliferation and intercellular adhesion. We developed a transgenic mouse model to assess leukosialin's function in vivo. Our approach was to alter mouse CD43 Leukosialin [also designated as CD43, sialophorin and large sialoglycoprotein in humans, Ly48 or mouse CD43 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…In the B-cell lineage, CD43 is present on the cell surface of terminally differentiated cells causing prolonged survival, but not in less-differentiated cells (Dragone et al, 1995;Rosenstein et al, 1999). The reason for CD43 not being studied in other cell types is that CD43 has long been considered as an exclusive leukocyte marker.…”
Section: Introductionmentioning
confidence: 99%
“…In the B-cell lineage, CD43 is present on the cell surface of terminally differentiated cells causing prolonged survival, but not in less-differentiated cells (Dragone et al, 1995;Rosenstein et al, 1999). The reason for CD43 not being studied in other cell types is that CD43 has long been considered as an exclusive leukocyte marker.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement of CD43 in leukocyte homing and tissue infiltration, possibly due to its adhesive or anti-adhesive properties, has been shown in several studies (19,25,26). It has also been demonstrated that CD43 can regulate cell survival (27,28) and is involved in the apoptosis of T cells and hemopoietic progenitor cells (29 -32).…”
mentioning
confidence: 99%
“…This function is achieved by virtue of the size and strong negative charge of the extracellular domain. [15][16][17][18] During leukocyte activation, CD43 expression is dramatically down-regulated, allowing intercellular interactions mediated by molecules such as the ␀ 2 integrins. Intercellular interactions are also actively facilitated by CD43, which, due to changes in glycosylation, switches from being an antiadhesion to a proadhesion molecule.…”
Section: Introductionmentioning
confidence: 99%